2011
DOI: 10.1007/s10236-011-0506-4
|View full text |Cite
|
Sign up to set email alerts
|

Improving hydrodynamic modeling of an estuary in a mixed tidal regime by grid refining and aligning

Abstract: Water levels and flows in the Singapore coastal waters are driven by the complex interactions of the Indian and Pacific Ocean tides, seasonal monsoon-driven contributions and also forced by local winds. The Singapore Regional Model was developed to simulate hydrodynamics in the Strait of Singapore which produces representative sea level variation in this region. However, resolution and alignment of the grid system of the model with respect to depth contours in some of its subregions, i.e., the Johor Estuary ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…However, the improvement in accuracy was usually restricted to only small simulated area (showed in [25,32]) or was not obvious in tidal current and water level simulations (showed in [19]). In comparison, by refining the local mesh resolution according to the local geometry can effectively improve the water levels and tidal currents simulation as proven in various studies (refer to studies by [9,21]), which it is also suggested to be a crucial element in the sensitivity analysis of SCW tidal simulations conducted by Kurniawan et al [22] and Sun et al [27].…”
Section: Introduction and Motivation Statementmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the improvement in accuracy was usually restricted to only small simulated area (showed in [25,32]) or was not obvious in tidal current and water level simulations (showed in [19]). In comparison, by refining the local mesh resolution according to the local geometry can effectively improve the water levels and tidal currents simulation as proven in various studies (refer to studies by [9,21]), which it is also suggested to be a crucial element in the sensitivity analysis of SCW tidal simulations conducted by Kurniawan et al [22] and Sun et al [27].…”
Section: Introduction and Motivation Statementmentioning
confidence: 99%
“…Delft3D, MIKE, POM and FVCOM) have been intensely conducted since last two decades. Among them, most studies were done using either two-dimensional [4,19,27,28] or threedimensional models [3,30,31]. Among those models, the most common meshing method involved orthogonal or regular rectangular grids (as the fully unstructured grid model is computationally too demanding to apply for large-scale coastal flow application as suggested in [29]); and the boundary conditions were usually set by effective water depth.…”
Section: Introduction and Motivation Statementmentioning
confidence: 99%
See 3 more Smart Citations